73.3k views
5 votes
Simplify (10x^2-19x-2) + (5x^2-8x+13) - (3x^2-2)

User Chgad
by
5.9k points

1 Answer

4 votes

Greetings!

Answer:

12x² -27x + 13

Explanation:

First of all, expand the first two brackets and put the correlating values near each other:

10x² + 5x² -19x -8x -2 +13

10x² + 5x² = 15x²

-19x + - 8x = -27x

-2 + 13 = 11

15x² - 27x + 11

Now, subtract the values inside the third bracket:

15x² - 3x² = 12x²

11 - -2 = 11 + 2 = 13

So the end result is:

12x² -27x + 13


Hope this helps!


User Juniel
by
6.1k points